Application of FIFA 11+ Kids: Method to minimize sports injuries in youth football - Khoiril Anam; Limpad Nurrachmad; Anies Setiowati; Nanang Indardi; Yuwono; Fajar Awang Irawan; Preeyaporn Gulsirirat; Nugroho Susanto; Nuridin Widya Pranoto (Journal Sport Area, 2022)
Football is one of the sports with the highest risk of injury, with injuries to children around 3% per year with serious injuries occurring at only 0.69% per year. The objective of the study is to investigate the application of FIFA 11+ Kids in minimizing sports injuries in youth football through enhancement components of physical condition, namely, leg muscle power and muscle flexibility. This study is an quasi-experimental research by using a pre-test - post-test control group design. The sample in this study are 20 people, divided into control and treatment groups. In this study, the sample is determined using a purposive sampling technique, with the following inclusion criteria: 1) male, 2) 11-12 years old, 3) practicing football regularly, 3) willing to be a research sample. In contrast, the criteria exclusion is experienced injured and unwilling to be a research sample. The distribution of control and treatment groups using matching subject ABBA technique. Instruments used in this research are the standing broad jump test to measure leg muscle power and sit and reach test to measure muscle flexibility. The data analysis is a t-test regression analysis with a level of 5% significance. This study found that the application of FIFA 11+ Kids can be used as a method to minimize sports injuries in youth football. The limitation of this study is that the sample is limited to only 20 children. This research is important because it contributes to the science of football coaching in terms of preventing injuries to children. Future research is expected to thoroughly examine the components of other physical conditions related to injury prevention, and use a larger sample from various age groups of soccer school students.